Calcium abundances of blue horizontal branch stars in ω Centauri. - D'Cruz, N. L.; Dickens, R. J.; Hatzidimitriou, D.; Rood, R. T.; O'Connell, R. W. (1997)
Spectra of 480 blue horizontal branch (BHB) stars in ω Centauri have been obtained using the multiobject fiber spectroscopic facility, Autofib, at the 3.9 m AAT. Preliminary analysis in the temperature range 7500K - 8200K indicates that a large fraction of BHB stars are at lower metallicities compared to the RR Lyrae stars and the giants. This could possibly be used to elucidate how mass loss efficiency varies with metallicity. The data can also be used together with simulated HBs to derive the variation of HB luminosity with metallicity.
Keywords: Globular Clusters: Horizontal-Branch Stars; Globular Clusters: Metal Abundances